2010
DOI: 10.1002/iroh.201011234
|View full text |Cite
|
Sign up to set email alerts
|

Food Web and Trophic Basis of Production of the Benthic Macroinvertebrate Community of a Subtropical Stream (Yangtze River Basin, Middle China)

Abstract: The food web of the benthic macroinvertebrate community of the Tanqigou Stream -a subtropical forested headwater stream of the Yangtze River basin -was investigated for the first time. The results indicated that the stream was mainly a detritus-based system, with its functionality being highly dependent on allochthonous input of organic matter. Vascular plant detritus, filamentous algae, diatoms and fungi were also important food resources for the macroinvertebrate community in the stream. Temporal and spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In addition to shading, frequent high discharge events in tropical streams like Río Guabal result in significant scouring of algal resources (Salas & Dudgeon, ). Studies in a Chinese subtropical river found percentages of autochthonous material in macroinvertebrate diets similar to those we observed in Río Guabal, and attributed both canopy cover and scouring to lower overall consumption of autochthonous resources (Wen et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In addition to shading, frequent high discharge events in tropical streams like Río Guabal result in significant scouring of algal resources (Salas & Dudgeon, ). Studies in a Chinese subtropical river found percentages of autochthonous material in macroinvertebrate diets similar to those we observed in Río Guabal, and attributed both canopy cover and scouring to lower overall consumption of autochthonous resources (Wen et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Wen et al () studied macroinvertebrate food webs in the Tanqigou Stream, a 2nd order stream in the Yangtze River basin. Similarly, amorphous detritus was also the major food source, consumed at a rate of 16.88 g m −2 yr −1 by the macroinvertebrate assemblage, comprising 81% of the total consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonality is an indirect factor that influences macroinvertebrate communities via integrated changes of discharge, food availability, temperature and other variables (Leung & Dudgeon, 2011;Silveira, Buss, Nessimian, & Baptista, 2006;Wen et al, 2010). We postulated that the proportion of each food type found in the guts of macroinvertebrates would vary from season to season, and that the seasonal variation patterns might differ between stream orders.…”
Section: Temporal Patterns Of Ingestionmentioning
confidence: 99%
See 1 more Smart Citation
“…Premke et al (2010) found that littoral benthic fauna are mainly supported by benthic algae in low-dissolved organic carbon (DOC) lakes and by phytoplankton and allochthonous organic C in high-DOC lakes, as a result of light absorbance and energy supply by allochthonous organic C. An investiagation of the Tanqigou Stream (Yangtze River basin) showed that the stream was mainly a detritus-based system, with its functionality being highly dependent on allochthonous input of organic matter. Benthic algae, fungi and vascular plant detritus, were also important food resources for macroinvertebrates (Wen et al, 2010). On the other hand, the dominant primary consumers (chironomids) in aquatic food webs in the Canadian High Arctic were supported primarily by benthic algae.…”
Section: Competition With and Facilitation Bymentioning
confidence: 99%